Boldine-Derived Alkaloids Inhibit the Activity of DNA Topoisomerase I and Growth of Mycobacterium tuberculosis - García, María T.; Carreño, David; Tirado-Vélez, José M.; Ferrándiz, María J.; Rodrigues, Liliana; Gracia, Begoña; Amblar, Mónica; Ainsa, José A.; de la Campa, Adela G. (Frontiers in Microbiology, 2018)
The spread of multidrug-resistant isolates of Mycobacterium tuberculosis requires the discovery of new drugs directed to new targets. In this study, we investigated the activity of two boldine-derived alkaloids, seconeolitsine (SCN) and N-methyl-seconeolitsine (N-SCN), against M. tuberculosis. These compounds have been shown to target DNA topoisomerase I enzyme and inhibit growth of Streptococcus pneumoniae. Both SCN and N-SCN inhibited M. tuberculosis growth at 1.95 to 15.6 microM, depending on the strain. In M. smegmatis this inhibitory effect correlated with the amount of topoisomerase I in the cell, hence demonstrating that this enzyme is the target for these alkaloids in mycobacteria. The gene coding for topoisomerase I of strain H37Rv (MtbTopoI) was cloned into pQE1 plasmid of Escherichia coli. MtbTopoI was overexpressed with an N-terminal 6-His-tag and purified by affinity chromatography. In vitro inhibition of MtbTopoI activity by SCN and N-SCN was tested using a plasmid relaxation assay. Both SCN and N-SCN inhibited 50% of the enzymatic activity at 5.6 and 8.4 microM, respectively. Cleavage of single-stranded DNA was also inhibited with SCN. The effects on DNA supercoiling were also evaluated in vivo in plasmid-containing cultures of M. tuberculosis. Plasmid supercoiling densities were −0.060 in cells untreated or treated with boldine, and −0.072 in 1 x MIC N-SCN treated cells, respectively, indicating that the plasmid became hypernegatively-supercoiled in the presence of N-SCN. Altogether, these results demonstrate that the M. tuberculosis topoisomerase I enzyme is an attractive drug target, and that SCN and N-SCN are promising lead compounds for drug development.